SDSS-IV MaNGA: Spectroscopic Probes of Neutral Gas in Nearby Galaxies - Machuca, Camilo; Bershady, Matthew A.; Rubin, Kate H. R.; Wilcots, Eric (The Astrophysical journal, 2025)
Cool, dusty interstellar material plays an important role in the chemical evolution of galaxies. We present an analysis of this material across galaxy type through a spatially resolved spectral stacking analysis of galaxies from the MaNGA survey. With stellar population synthesis, we isolate neutral gas signals from resonance lines, comparing outcomes across model types, galactic geometry, and host stellar mass and age. We find that both synthetic and empirical models fail to capture the range of galactic chemical abundances. There is also notable Na i contamination from the Galaxy’s interstellar medium (ISM) in the MILES empirical stellar library. We are unable to reliably determine the column density of the gas due to the accuracy of absorption measurements, but differential analysis across radius and inclination reveals consistent and significant path-length dependent absorption in the equivalent width of Na i . We note similar but lesser trends in a narrow Ca ii index. We find no trends in Ca i or in a broad Ca ii index, indicating its ISM insensitivity and providing evidence in favor of its utility in determining the age and chemical content of stellar populations. Our data shows there is a cool ISM component in most external galaxies with D n (4000) < 1.7 that can be traced by Na i . Lastly, we caution that the characterization of gas kinematics traced by Na i in such low-resolution spectra is subject to systematic effects due to the chosen approach to stellar population modeling.